Optimizing the pulse shape for Schwinger pair production - Kohlfürst, Christian; Mitter, Mario; Winckel, Gregory von; Hebenstreit, Florian; Alkofer, R. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
Recent studies of the dynamically assisted Schwinger effect have shown that particle production is significantly enhanced by a proper choice of the electric field. We demonstrate that optimal control theory provides a systematic means of modifying the pulse shape in order to maximize the particle yield. We employ the quantum kinetic framework and derive the relevant optimal control equations. By means of simple examples we discuss several important issues of the optimization procedure such as constraints, initial conditions or scaling. By relating our findings to established results we demonstrate that the particle yield is systematically maximized by this procedure.